Expression, purification, crystallization and preliminary X-ray diffraction analysis of rhesus macaque CD8αα homodimer - Zong, Lili (International Union of Crystallography, 2010)
As a T-cell co-receptor, CD8 binds to MHC class I molecules and plays a pivotal role in the activation of cytotoxic T lymphocytes. To date, structures of CD8 have been solved for two different mammals: human and mouse. The infection of rhesus macaques (Macaca mulatta) by simian immunodeficiency virus (SIV) is the best animal model for studying HIV. In this study, the rhesus macaque CD8 (rCD8) αα homodimer was obtained and rCD8α exodomain protein crystals were successfully obtained for further structural analysis. Diffraction data were collected to a resolution of 2.4 Å. The crystal belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 46.52, b = 56.28, c = 82.40 Å. These data will facilitate further studies on the structural differences between these CD8 structures and the cellular immune responses of rhesus macaque.